Application of Financial Flow Simulator (eSOSView™) for Analyzing Financial Viability and Developing a Sustainable Fecal Sludge Management Business Model in Kushtia, Bangladesh - Akbar Chinna Mohideen, Sheik Mohammed Shibl; Singh, Shirish; Chowdhury, Tanvir Ahamed; Brdjanovic, Damir (Frontiers in Environmental Science, 2022)
To achieve SDG 6.2.1 (a) on safely managed sanitation services, several Financial Flow Models (FFMs) and business models for sanitation value chain have been implemented in Bangladesh and elsewhere, however, there is limited research on financial viability and sustainability of business models. Bangladesh has attained 99% sanitation coverage, mostly with onsite sanitation systems however, the country is facing a second-generation sanitation challenge, faecal sludge management, encompassing entire sanitation chain. Kushtia municipality in Bangladesh, is entirely served by onsite systems, faecal sludge emptying service is provided by the municipality and faecal sludge treatment plant is managed by a private entity. This study investigated sustainability of FFMs in Kushtia by using Financial, Institutional, Environmental, Technical and Social (FIETS) sustainability approach and applying Financial Flow Simulator (eSOSView™) tool to analyze financial viability. Several criteria in each aspect of the FIETS approach were developed, scored, and validated by stakeholders to determine sustainability. The study found that financial aspect is the most important criteria for sustainability and “Modified Parallel tax and Discharge Fee” is the most sustainable business model for Kushtia.